A novel saponin liposomes based on the couplet medicines of Platycodon grandiflorum–Glycyrrhiza uralensis for targeting lung cancer. (31st December 2022) - Guo, Chunjing; Su, Yanguo; Wang, Hui; Cao, Min; Diao, Ningning; Liu, Zhongxin; Chen, Daquan; Kong, Ming
Abstract: Liposomes have been widely used for targeted drug delivery, but the disadvantages caused by cholesterol limit the application of conventional liposomes in cancer treatment. The compatibility basis of couplet medicines and the compatibility principle of the traditional Chinese medicine principle of 'monarch, minister, assistant and guide' are the important theoretical basis of Chinese medicine in the treatment of tumor and the important method to solve the problem of high toxicity. In this study, the active ingredients of the couplet medicines Platycodon grandiflorum and Glycyrrhiza uralensis were innovatively utilized, and glycyrrhizic acid (GA) was encapsulated in liposomes constructed by mixing saponin and lecithin, and cholesterol was replaced by platycodin and ginsenoside to construct saponin liposomes (RP-lipo) for the drug delivery system of Chinese medicine. Compared with conventional liposomes, PR-lipo@GA has no significant difference in morphological characteristics and drug release behavior, and also shows stronger targeting of lung cancer cells and anti-tumor ability in vitro, which may be related to the pharmacological properties of saponins themselves. Thus, PR-lipo@GA not only innovatively challenges the status of cholesterol as a liposome component, but also provides another innovative potential system with multiple functions for the clinical application of TCM couplet medicines.